2018
DOI: 10.1016/j.fertnstert.2017.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin as a new serum biomarker to discriminate miscarriage from viable intrauterine pregnancy

Abstract: Plasma levels of kisspeptin have been suggested as a biomarker for miscarriage. This study demonstrates kisspeptin assay stability in serum and its potential clinical utility as a biomarker for early pregnancy viability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 21 publications
2
41
1
1
Order By: Relevance
“…It is well known that maternal serum hCG peaks at 8–10 weeks of gestation and then declines to reach a plateau at 18–20 weeks of gestation, while the level of KP continues to rise throughout gestation into the 3rd trimester and, unlike hCG, does not plateau . No substantial correlation between KP and hCG rates in viable intrauterine pregnancy, whereas in spontaneous abortions there is a significant correlation between KP and hCG levels …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that maternal serum hCG peaks at 8–10 weeks of gestation and then declines to reach a plateau at 18–20 weeks of gestation, while the level of KP continues to rise throughout gestation into the 3rd trimester and, unlike hCG, does not plateau . No substantial correlation between KP and hCG rates in viable intrauterine pregnancy, whereas in spontaneous abortions there is a significant correlation between KP and hCG levels …”
Section: Discussionmentioning
confidence: 99%
“…There is a strict relationship between pregnancy‐induced hypertension and elevated serum β‐hCG levels, indicating that there should be an abnormal placental secretary function in patients with severe PE . Therefore, sequential serum hCG values and transvaginal ultrasound tests are used to determine the feasibility of childbirth . Thus, KP is now known as an emerging biomarker for the discrimination of viable pregnancy due to its potential regulatory role in trophoblast function and placentation …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, inappropriately low kisspeptin levels have been proposed as biomarker of gestational alterations, such as intrauterine growth restriction and preeclampsia (22,23), and putative predictor of miscarriage risk (24). In fact, a very recent study comparing a well-defined, as yet limited (N=20), population of women with viable intrauterine pregnancy vs. women with confirmed spontaneous abortion suggested that kisspeptin levels during an early gestational window (weeks 6-10) might serve as good biomarker of pregnancy viability (25). However, to our knowledge, no single study has addressed potential dynamic changes in KISS1/kisspeptin in EP, and their eventual diagnostic utility in this condition.…”
Section: Introductionmentioning
confidence: 99%
“…11 It should be noted that the expression of KISS1 in the placenta or plasma kisspeptin levels may be affected by the adverse uterine environment. 12,13 Plasma or serum kisspeptin levels are significantly increased in early pregnancy compared to non-pregnant controls. [13][14][15]…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Plasma or serum kisspeptin levels are significantly increased in early pregnancy compared to non-pregnant controls. [13][14][15]…”
Section: Introductionmentioning
confidence: 99%